Análise de estabilidade global em estruturas de edifícios em concreto armado - Silva, Guilherme Henrique Melo (2018)
This paper presents a study about the global stability of reinforced concrete buildings. Presenting the three important methods of analysis of the overall stability of buildings according to ABNT NBR 6118: 2014: Parameter α, coefficient yZ and P-Delta process. There are presented parametric analyzes of a structural model in reinforced concrete are presented with second order effects considerations. Analyzing the amplitude of the effects of second order by changing the class of concrete used in the structural design, always considering the physical and geometric nonlinearities of the material and the structure. It also relates and compares if the requests obtained through the iterative PDelta process with the approximation suggested by ABNT NBR 6118: 2014, the increase of the coeficiente yZ. Conclude that the more rigid the structure, the smaller the difference between the first and second order analyzes (P-delta).